The Understanding of Istita‘ah concept in Hajj through financing schemes among ACIS staff in UiTM Puncak Alam / Nor Afiqah Nazihah Mohamad Roslan. - Mohamad Roslan, Nor Afiqah Nazihah (2019)
A lack of knowledge regarding the concept of istita'ah is a reason why people do not take advantage of the opportunity and the hajj financing schemes are not widely known. This is a case study which studied the understanding of the istita‘ah concept in hajj through financing schemes. This study carried out in one of the universities in Selangor which is has been specified to the ACIS staff in UiTM Puncak Alam. As many of 12 sets of the questionnaire as required have been distributed to accomplish this study. Briefly, it has been using the quantitative measurement for data collection which involved three sections according to the research questions. The data was analysed using Statistical Package for Social Science (IBM SPSS 20). According to the results, it illustrates that the understanding of the istita‘ah concept in hajj through financing schemes at a moderate level. It looks like many Muslims communities are lack of knowledge about the schemes. However, they seem interested and intended to grab the opportunity for the future after knowing it. This study offers disclosure to the communities to get the financing schemes that allowed in Shari’ah. If the public can see that this is one of the opportunities for those who cannot afford it at a young age, then the consumption of hajj financing will be much more widely be known and accepted. In fact, the problem is that many pilgrims comprise of the elderly who are unable to perform the pilgrimage completely. At that time, their amount of money is pretty enough but lacking in terms of health and energy to perform the perfect worship. Muslims or depositors should meet the requirement before taking the financing and the failure to do so, they are included people who inability and it is not listed in the characteristics of ability (istita'ah). Inability makes them disqualified to get the financing provided. So, whoever are no matters with the ability of health and mental, enables them to perform hajj through that financing as they meet the conditions and in accordance with Shari’ah.